Effect of Perillaldehyde on Prophylaxis and Treatment of Vaginal Candidiasis in a Murine Model - Qu, Su; Chen, Lei; Tian, Hui; Wang, Zhen; Wang, Fei; Wang, Liqin; Li, Jinting; Ji, Hui; Xi, Liurong; Feng, Zhaojun; Tian, Jun; Feng, Zhaozhong (Frontiers in Microbiology, 2019)
Vulvovaginal candidiasis is a common fungal infection afflicting women that is primarily caused by the yeast Candida albicans (C. albicans). It is imperative to introduce new drug classes to counter this threat due to the continuous emergence of drug-resistant cases in recent years. The purpose of this study was to clarify the in vivo antifungal activity of perillaldehyde (PAE) against C. albicans and to prove that PAE is a promising candidate for the control of vaginal candidiasis. An animal model of vaginitis was developed to demonstrate the therapeutic and preventive effects of PAE on vaginal candidiasis, and these were evaluated through fungal and histopathological examination. In clarifying the mechanism of PAE, standard hematological test results indicated that white blood cells (WBC) were elevated abnormally in mice infected with C. albicans, whereas when the mice were treated with various concentrations of PAE, the number of WBC in the blood was reduced. Flow cytometry was used to detect the populations of neutrophils, macrophages and CD4 T cells in the vaginal tissue of the mice. PAE was found to reduce these immune cells, which all play a key role in the inflammatory response, and the related interleukin and pro-inflammatory cytokines, including IL-17, IL-22 and TNF-α. These were detected by using ELISA. Finally, we detected the expression levels of E-cadherin in the PAE treatment group mice and discovered it had recovered to its normal levels, but in the infection group mice, the E-cadherin expression was clearly suppressed by the presence of C. albicans. Our data demonstrated that PAE targets these cytokines and possesses the ability to fight the fungal infection while also reducing the levels of the inflammatory factors identified. Our results demonstrated that PAE has a significant preventative and therapeutic effect on vaginal candidiasis and is a potential candidate for the treatment of vaginal Candida infections.